2009
DOI: 10.1111/j.1365-2966.2008.14149.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between instability and Lyapunov times for the three-body problem

Abstract: In this study we consider the relationship between the survival time and the Lyapunov time for three‐body systems. It is shown that the Sitnikov problem exhibits a two‐part power‐law relationship as demonstrated by Mikkola & Tanikawa for the general three‐body problem. Using an approximate Poincaré map on an appropriate surface of section, we delineate escape regions in a domain of initial conditions and use these regions to analytically obtain a new functional relationship between the Lyapunov time and the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 10 publications
(26 reference statements)
4
18
2
Order By: Relevance
“…For long decay times (100, 000T cr < T < 1, 000, 000T cr ), this distribution is approximately a power law, f (T ) ∝ T −α , with α ≈ 1.74. This result qualitatively agrees with the results of other studies [6][7][8][9][10].…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…For long decay times (100, 000T cr < T < 1, 000, 000T cr ), this distribution is approximately a power law, f (T ) ∝ T −α , with α ≈ 1.74. This result qualitatively agrees with the results of other studies [6][7][8][9][10].…”
Section: Resultssupporting
confidence: 95%
“…This figure also shows two fits to f (T ): an exponential function (solid curve) and a power law (dashed curve). We can see from the figure that the power-law provides a much better fit than the exponential, in agreement with the earlier studies [6][7][8][9][10]. The power-law index α = 1.74 is located within the range obtained in [6][7][8][9][10], from 1.4 to 2.2.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Urminsky & Heggie (2009) demonstrated that the Poincaré map ϕ with can be approximated by a simplectic map φ : ( t 0 , E 0 ) → (t 1 , E 1 ) where and a , b and C are constants. The quantities t 1/2 and E 1/2 are approximations of the time and energy values of m 3 at a local maximum distance from the SOS.…”
Section: The Sitnikov Problemmentioning
confidence: 99%
“…Urminsky and Heggie (2009) used the Poincaré surface of section of the three-body problem to refine the values of these constants. However, Milani and coworkers (Milani & Nobili 1992;Milani et al 1997) argued against the idea of this simple relation by drawing attention to the discovery of asteroids with short T L that do not become planet crossers, nor exhibit any large radial variations, for a thousand times the T L .…”
Section: Introductionmentioning
confidence: 99%